Dukungan Sosial dalam Membentuk Resiliensi pada Orang dengan Lupus (ODAPUS) - Lia Arina Rahmawati; Diyah Sulistiyorini; Moh. Bisri (Jurnal Penelitian Kualitatif Ilmu Perilaku, 2021)
This study used qualitative methods with case study techniques. Subjects were 2 women and 1 subject male who was of productive age and had survived with lupus for a long time and had been declared remission healed. In this study data collection was carried out with techniques in-depth interviews with the research subjects in order to obtain the information needed. Checking the validity of the data was examined by using significant other re-checks and triangulation with people. As for the location of the research conducted in the city of Malang. The results showed that resilience on Odapus was influenced by the support given by the closest people, especially the nuclear family. The form of social support that seemed more influential was emotional support and appreciation. In addition, it is undeniable that instrumental support is also important for Odapus considering the amount of costs needed for Odapus treatment.